2015
DOI: 10.1515/hukin-2015-0030
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability of Electromyographic Normalization Methods for Cycling Analyses

Abstract: Electromyography (EMG) is normalized in relation to a reference maximum voluntary contraction (MVC) value. Different normalization techniques are available but the most reliable method for cycling movements is unknown. This study investigated the reliability of different normalization techniques for cycling analyses. Twenty-five male cyclists (age 24.13 ± 2.79 years, body height 176.22 ± 4.87 cm and body mass 67.23 ± 4.19 kg, BMI = 21.70 ± 2.60 kg·m-1) performed different normalization procedures on two occasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…We also considered using maximal voluntary isometric contractions for EMG normalization, but this method has been criticized for not being suitable for EMG normalization during cycling (Hug & Dorel, 2009). Furthermore, recent studies showed that normalizing EMG amplitudes using peak EMG values from a submaximal condition during cycling demonstrated higher reliability and sensitivity in EMG outcomes for lower extremity muscles compared to normalization using a maximal isometric voluntary contraction (Albertus-Kajee, Tucker, Derman, & Lambert, 2010;Sinclair et al, 2015). The onsets and offsets of normalized EMG activity of each muscle during cycling trials were determined using a Teager-Kaiser energy operator (TKEO), which reduces background noise and enhances signal-to-noise ratio (Solnik, Rider, Steinweg, DeVita, & Hortobagyi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…We also considered using maximal voluntary isometric contractions for EMG normalization, but this method has been criticized for not being suitable for EMG normalization during cycling (Hug & Dorel, 2009). Furthermore, recent studies showed that normalizing EMG amplitudes using peak EMG values from a submaximal condition during cycling demonstrated higher reliability and sensitivity in EMG outcomes for lower extremity muscles compared to normalization using a maximal isometric voluntary contraction (Albertus-Kajee, Tucker, Derman, & Lambert, 2010;Sinclair et al, 2015). The onsets and offsets of normalized EMG activity of each muscle during cycling trials were determined using a Teager-Kaiser energy operator (TKEO), which reduces background noise and enhances signal-to-noise ratio (Solnik, Rider, Steinweg, DeVita, & Hortobagyi, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The normalization method calculates the amplitude ratio of the measured surface EMG signals to those at the MVC. All drivers were trained to perform the MVC before the tests (Sinclair et al, 2015).…”
Section: Figure 3 Measurement Of Surface Emg Signals From Shoulder Mmentioning
confidence: 99%
“…A normalização eletromiográfica da função muscular pelo apertamento dental em contração voluntária máxima foi um fator importante necessário para determinar a correta interpretação dos dados de comparação entre diferentes indivíduos, músculos e dias de coletas o qual minimizou as diferenças existentes, mesmo pareando sujeito a sujeito por idade, gênero, peso e altura (Botelho et al, 2011;Rabita et al, 2000;Sinclair et al, 2015;Schwartz et al, 2017 Garg, 2016;Fraiwan et al, 2016;Yakabi et al, 2017).…”
Section: Discussionunclassified